Math, asked by rohitmanda9964, 4 months ago

Find the square root of the following surds
12+2root 35
8-2root 15
31-4root 21
30+12root 6

Answers

Answered by IntrovertLeo
6

Given:

\bf 1. \: 12+2\sqrt{35}

\bf 2. \: 8-2\sqrt{15}

\bf 3. \: 31-4\sqrt{21}

\bf 4. \: 30+12\sqrt{6}

What To Find:

We have to find -

  • The square root of the given surds.

How To Find:

To find, we have to -

  • First, write in the form of \sf \sqrt{a}+\sqrt{b}.
  • Next. square the sides by using identities.
  • Then, find the square roots of the expression.

Answer 1:

\sf 12+2\sqrt{35}

Take it in the form of \sf \sqrt{a}+\sqrt{b} and write it as,

\sf \to \sqrt{a}+\sqrt{b} = \sqrt{12+2\sqrt{35}}

Square both sides,

\sf \to (\sqrt{a}+\sqrt{b})^2 = \bigg(\sqrt{12+2\sqrt{35}}\bigg)^2

Square the LHS by using the identity,

\sf \to (\sqrt{a}+\sqrt{b})^2 = a + b + 2\sqrt{ab}

Square the RHS by cancelling the surds and powers,

\sf \to\bigg(\sqrt{12+2\sqrt{35}}\bigg)^2 = 12+2\sqrt{35}

After squaring both sides,

\sf \to a + b + 2\sqrt{ab} = 12 + 2\sqrt{35}

Let's take -

  • a + b = 12
  • 2√ab = 2√35

Cancel 2 from both sides,

  • √ab = √35

On squaring,

  • (√ab)² = (√35)²
  • ab - 35

By manual guess,

  • a + b = 12 = 7 + 5
  • ab = 35 = 7 × 5

∴ Thus, the answer is:-  \bf \sqrt{7}+\sqrt{5}.

Answer 2:

\sf 8-2\sqrt{15}

Take it in the form of \sf \sqrt{a}+\sqrt{b} and write it as,

\sf \to \sqrt{a}+\sqrt{b} = \sqrt{8-2\sqrt{15}}

Square both sides,

\sf \to (\sqrt{a}+\sqrt{b})^2 = \bigg(\sqrt{8-2\sqrt{15}}\bigg)^2

Square the LHS by using the identity,

\sf \to (\sqrt{a}+\sqrt{b})^2 = a + b + 2\sqrt{ab}

Square the RHS by cancelling the surds and powers,

\sf \to\bigg(\sqrt{8-2\sqrt{15}}\bigg)^2 = 8-2\sqrt{15}

After squaring both sides,

\sf \to a + b + 2\sqrt{ab} = 8-2\sqrt{15}

Let's take -

  • a + b = 8
  • 2√ab = 2√15

Cancel 2 from both sides,

  • √ab = √15

On squaring,

  • (√ab)² = (√15)
  • ab = 15

By manual guess,

  • a + b = 8 = 5 + 3
  • ab = 15 = 5 × 3

∴ Thus, the answer is:- \bf \sqrt{5} + \sqrt{3}

Answer 3:

\sf 31-4\sqrt{21}

Take it in the form of \sf \sqrt{a}+\sqrt{b} and write it as,

\sf \to \sqrt{a}+\sqrt{b} = \sqrt{31-4\sqrt{21}}

Square both sides,

\sf \to (\sqrt{a}+\sqrt{b})^2 = \bigg(\sqrt{31-4\sqrt{21}}\bigg)^2

Square the LHS by using the identity,

\sf \to (\sqrt{a}+\sqrt{b})^2 = a + b + 2\sqrt{ab}

Square the RHS by cancelling the surds and powers,

\sf \to\bigg(\sqrt{31-4\sqrt{21}}\bigg)^2 = 31-4\sqrt{21}

After squaring both sides,

\sf \to a + b + 2\sqrt{ab} = 31-4\sqrt{21}

Let's take -

  • a + b = 31
  • 2√ab = 4√21

Cancel 2 from both sides,

  • √ab = 2√21

Squaring both sides,

  • (ab)² = (2√21)²
  • ab = 84

By manual guess,

  • a + b = 31 = 28 + 3
  • ab = 84 = 28 × 3

∴ Thus, the answer is:- \bf \sqrt{28}+\sqrt{3} or  \bf 2\sqrt{7} + \sqrt{3}

Answer 4:

\sf 30+12\sqrt{6}

Take it in the form of \sf \sqrt{a}+\sqrt{b} and write it as,

\sf \to \sqrt{a}+\sqrt{b} = \sqrt{30+12\sqrt{6}}

Square both sides,

\sf \to (\sqrt{a}+\sqrt{b})^2 = \bigg(\sqrt{30+2\sqrt{6}}\bigg)^2

Square the LHS by using the identity,

\sf \to (\sqrt{a}+\sqrt{b})^2 = a + b + 2\sqrt{ab}

Square the RHS by cancelling the surds and powers,

\sf \to\bigg(\sqrt{30+12\sqrt{6}}\bigg)^2 = 30+12\sqrt{6}

After squaring both sides,

\sf \to a + b + 2\sqrt{ab} = 30+12\sqrt{6}

Let's take -

  • a + b = 30
  • 2√ab = 12√6

Cancel 2 from both sides,

  • ab = 6√6

Squaring both sides,

  • (√ab)² = (6√6)²
  • ab = 216

By manual guess,

  • a + b = 30 = 12 + 18
  • ab = 216 = 28 × 3

∴ Thus, the answer is:- \bf \sqrt{18} + \sqrt{12} or  \bf 3\sqrt{2} + 2\sqrt{3}

Similar questions